Ruminant physiology [ digestion, metabolism, growth, and reproduction - Boomker, E. A.; Cronje',P. [ (Pierre)] (CABI Publishing, 2000)
The International Symposium on Ruminant Physiology (ISRP) is the premier forum for presentation and discussion of advances in knowledge of the physiology of ruminant animals. This book brings together edited versions of the keynote review papers presentd at the symposium.